Inheritance of resistance to bacterial blight in 21 cultivars of rice - Lee, K.S.; Rasabandith, S.; Angeles, E.R.; Khush, G.S. (Scientific Societies, 2003)
Genetic analysis for resistance to bacterial blight (Xanthomonas oryzae pv. oryzae) of 21 rice (Oryza sativa L.) cultivars was carried out. These cultivars were divided into two groups based on their reactions to Philippine races of bacterial blight. Cultivars of group 1 were resistant to race 1 and those of group 2 were susceptible to race 1 but resistant to race 2. All the cultivars were crossed with TN1, which is susceptible to all the Philippine races of X. oryzae pv. oryzae. F1 and F2 populations of hybrids of group 1 cultivars were evaluated using race 1 and F1 and F2 populations of hybrids of group 2 cultivars were evaluated using race 2. All the cultivars showed monogenic inheritance of resistance. Allelic relationships of the genes were investigated by crossing these cultivars with different testers having single genes for resistance. Three cultivars have Xa4, another three have xa5, one has xa8, two have Xa3, eight have Xa10, and one has Xa4 as well as Xa10. Three cultivars have new, as yet undescribed, genes. Nep Bha Bong To has a new recessive gene for moderate resistance to races 1, 2, and 3 and resistance to race 5. This gene is designated xa26(t). Arai Raj has a dominant gene for resistance to race 2 which segregates independently of Xa10. This gene is designated as Xa27(t). Lota Sail has a recessive gene for resistance to race 2 which segregates independently of Xa10. This gene is designated as xa28(t).